Microbial production of succinic acid using crude and purified glycerol from a Crotalaria juncea based biorefinery - Suvra Sadhukhan; Raffaella Villa; Ujjaini Sarkar (Biotechnology Reports, 2016)
Microbial conversion of crude and purified glycerol obtained in the process of biorefining Crotalaria juncea is carried out to produce succinic acid using Escherichia coli. Batch tests are performed for nine different substrate concentrations of commercial, purified and crude glycerol, in order to observe cell growth and substrate utilization rate. Inhibitory (Halden-Andrew, Aiba-Edward, Tessier type and Andrews) as well as non-inhibitory (Monod, Moser and Tessier) models are fitted to the relationship between specific growth rate and substrate concentration obtained from the growth curves. Considering the inhibition effect, Aiba-Edward model ranked 1 out of 7 in case of two samples and Haldane-Andrew model ranked 1 in case of one sample. Aiba-Edward model gave the best fitment for a large range of concentrations of all the three types of glycerol, crude, purified and laboratory grade. Maximum production of succinic acid is obtained from commercial glycerol at pH 7 and 37.5 °C.